Pengaruh Kredit Usaha Rakyat Terhadap Pendapatan Usaha Mikro Dan Kecil Di Desa Selagik Kecamatan Terara Kabupaten Lombok Timur Provinsi Nusa Tenggara Barat (Studi Kasus Bank BRI Unit Terara) - Farhana Muhammad; Toyib Rozali (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2017)
This  research  was  aimed  at  knowing  the  effect  of  citizenry  exertion credit toward income of Micro and Small Exertion in Selagik, Kecamatan Terara,   abupaten  Lombok  Timur,  Provinsi  Nusa  Tenggara  Barat.  The approach  applied  was  quantitative  untilizing  deskcriptive  research.  The data  were  qualitative  data  and  quantitative  data  with  primary  data  and secondary as the data resource. Meanwhile, the data collection instrument applied  were  observation,  interview,  and  documentation.  The  data analyses  technique  applied  were  bifilar  regression  analysis,  classic assumption analysis, and compatibility testing consisted of 36 respondent of the Micro  and Small  Exertion (UMK)  agent.  The analysis instrument applied  was  SPSS  23.0  and  Microsoft  Exel  2007.  Based  on  the  result  of the  research,  it  showed  that  self  modal  and  Citizenry  Exertion  Credit (KUR)  modal  was  positively  affect  partially  and  simultaneously  toward Mikro  and  Small  Exertion  (UMK)  in  Selagik;  it  can  be  seen  from  the variable coefficient score stated.  Keywords : Micro and Small Exertion,Effect of Citizenry Exertion Credit